Are Neutrophil CD64 Expression and Interleukin-6 Early Useful Markers for Diagnosis of Acute Appendicitis? - Ozguner, İsmet F.; Kızılgun, Murat; Karaman, Ayse; Cavusoğlu, Yusuf Hakan; Erdoğan, Derya; Karaman, İbrahim; Afşarlar, Çağatay Evrim; Yılmaz, Engin (European Journal of Pediatric Surgery, 2014)
Background/Purpose The aim of the study is to evaluate the diagnostic value of interleukin-6 (IL-6) level and neutrophil cluster of differentiation 64 (CD64) expression in diagnosis of acute appendicitis (AA).Methods A prospective controlled trail was performed. Children who were hospitalized with a diagnosis of right lower quadrant pain were our cohort. Serum samples for white blood cell, C-reactive protein (CRP), leukocyte CD64 expression, and IL-6 were obtained from the patients just after their admission. Operation was performed if appendicitis seemed probable, others were observed actively. Patients who had noncomplicated appendicitis were Group 1, patients who had complicated appendicitis were Group 2, and patients who had discharged after observation without operation with a diagnosis of nonspecific abdominal pain and had negative appendectomy without another surgical disease were Group 3.Results In this study, 49 patients were enrolled. CRP and CD64 levels were found higher in Group 2. IL-6 levels were found to be lower in Group 3 than Groups 1 and 2.Conclusions There was a difference between Group 2 and the other groups about CD64 levels. The CRP level and expression of leukocyte CD64 level did not effectively predict the diagnosis of noncomplicated appendicitis, but it predicted well the patients with complicated appendicitis. However, IL-6 levels are statistically significantly different between Group 3 and Groups 1 and 2. According to this result, IL-6 levels predicted well the patient with appendicitis. Applying additional diagnostic methods such as IL-6 levels seems to be helpful in reducing the numbers of false-positive diagnosis of AA.
Keywords: appendicitis; interleukin-6; CD64 antigens; C-reactive protein; child